A 10-year US$50 million programme focused on crop wild relative collection and pre-breeding for climate change adaptation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS research demonstrated the threats posed to crop wild relatives by climate change and habitat conversion. Analyses showed the very poor conservation status of these gene pools. Based on this work, the Global Crop Diversity Trust made crop wild relative collecting a high priority activity. Thereafter, the Norwegian Government funded the Global Crop Diversity Trust and the Millennium Seed Bank Partnership, Kew, to establish the 10-year USD 50 million ‘Adapting agriculture to climate change: collecting, protecting and preparing crop wild relatives’ project focused on crop wild relative collection and pre-breeding for climate change adaptation. Strategic planning research for collecting activities was led by CIAT scientists in collaboration with the University of Birmingham. Regular discussions with the Global Crop Diversity Trust were fundamental in the prioritizing and design of the programme. The project aims to collect the wild relatives of 29 key crops, conserve the specimens in gene-banks, and prepare them for use in plant breeding programmes in time to breed new crop varieties adapted to new climates. The project commenced in 2011, and CIAT continues to provide support in defining priorities.